In vitro activity of ceftolozane/tazobactam against Gram-negative bacilli isolated from pediatric patients: Results from the Study for Monitoring Antimicrobial Resistance Trends (SMART) 2017–2021, China - Xinli Mu; Ying Fu; Pengcheng Li; Yunsong Yu (Journal of Global Antimicrobial Resistance, 2024)
ABSTRACT: Objectives: Ceftolozane-tazobactam (C/T) is a combination of a cephalosporin and a β-lactamase inhibitor with activity against Gram-negative bacilli (GNB). The study aims were to evaluate the activity of C/T in vitro vs. comparators against clinical GNB isolated from Chinese paediatric patients. Methods: From 2017–2021, 660 GNB isolates were collected from 20 hospitals across China. The minimum inhibitory concentrations were tested using a Trek Diagnostic System (Thermo Fisher Scientific). Susceptibility was determined by CLSI broth microdilution and the results were interpreted according to CLSI M100 (2021) breakpoints. Results: GNB isolates were obtained from paediatric patients < 18 years old, mainly from the bloodstream (n = 146), intraperitoneal cavity (n = 138), lower respiratory (n = 278) and urinary tract (n = 96). Overall, C/T was active against 76.6% of 436 Enterobacterales, with a descending susceptibility rate of 100.0% to S. marcescens, 92.2% to E. coli, 83.3% to K. oxytoca, 66.7% to K. aerogenes, 66.7% to P. mirabilis, 58.6% to K. pneumoniae and 57.1% to E. cloacae. The susceptibility of P. aeruginosa to C/T was 89.4%, which was the highest among the β-lactam antibiotics and was second only to amikacin (92.9%). Isolates of respiratory tract infection (RTI) derived P. aeruginosa were highly susceptible (93.8%) to C/T, while <75% of isolates of RTI derived P. aeruginosa were susceptible to the other β-lactam antibiotics tested, except for ceftazidime-avibactam (91.2%). Conclusion: GNBs collected from paediatric patients in China showed a high susceptibility to C/T making this drug combination an effective choice for treating the paediatric population, especially those infected with P. aeruginosa.